Global discourses and the local impacts in Amazonia. Inclusion and exclusion processes in the Rio Negro region - Neuburger, Martina (ERDKUNDE, 2008)
In the course of the climate change discussions, Amazonia, as the worlds largest continuous rain forest area, has achieved international attention. The significant role of the Amazon rain forest as the “green lung of the world’s climate” and its importance as an almost inexhaustible archive of biogenetic resources for the future development of the planet earth, are constantly accented. The conservation of rain forests is often spoken of in the same breath as the protection of indigenous peoples, and partially even put on the same level. The example of the Rio Negro region demonstrates clearly, how global discourses on climate change, the protection of forests and indigenous people are reflected on the local level via transmission tapes of unbalanced power relations. Forced by the powerful international discourses on these items, national discourses and regional policies concerning Amazonia have been shifted. Social groups, who are not clearly regarded as indigenous peoples or who do not match to the image of traditional, ecologically adapted ways of life, are largely ignored by the great variety of promotion instruments, as well as by national and international actors. In this way, international discourses define local life courses and decide what is “good” and “bad” or “right” and “wrong”. But, they do not embrace the complex reality of Amazonia and threaten the livelihoods of excluded social groups in peripheral regions.